The duality of hope and challenges: a phenomenological study of first-year university students’ experiences in South Africa - Mason, Henry D. (Frontiers in Psychology, 2024)
Introduction In South Africa, access to higher education is viewed as a pathway to improved life chances. However, the transition from school to university is a stressful experience for students, marked by significant challenges. Although literature acknowledges these challenges, limited research has focused specifically on the role of hope during this period. Additionally, previous studies on hope have often utilized individualistic approaches, which may not fully capture the experience of students in collectivist cultures. This study addresses this gap by exploring hope from a culturally sensitive perspective within a collectivist context, aiming to understand how first-year South African university students experience hope during the transition to university. Methods This study employed Interpretative Phenomenological Analysis (IPA) to explore the lived experiences of hope among first-year South African university students during their transition to higher education. Twenty-two students participated in semi-structured interviews, allowing for an in-depth examination of their personal and cultural perspectives on hope and the challenges they faced. The data were analyzed iteratively, with strategies implemented to enhance trustworthiness and credibility, ensuring a thorough interpretation of students’ experiences. Results The analysis yielded three main themes: (1) Affective and Social Duality: Students described mixed emotions and social challenges as they entered university, highlighting the dual nature of their experiences in adapting to a new environment. (2) Hope as a Multifaceted Concept: Hope was portrayed as a guiding force that helped students navigate periods of uncertainty. Participants described hope not just as a single idea but as a complex, evolving concept crucial to their resilience. (3) Beyond Academic Aspirations: Hope extended beyond academic success and was closely tied to personal fulfilment and the desire to contribute positively to society. This broader perspective on hope suggests that students’ aspirations were not confined to individual achievement but also included a sense of collective and societal impact. Discussion The study reveals that hope is a multidimensional construct that significantly influences students’ transitional experiences, extending beyond academic goals to include personal growth and societal contributions. This finding challenges the traditional, individualistic approaches to studying hope by highlighting the cultural relevance of collectivist values in shaping students’ experiences. The study underscores the need for culturally sensitive research and suggests that student support services should consider cultural contexts to address students’ unique challenges and aspirations better. Future research is recommended to explore hope across various cultural backgrounds to gain a more comprehensive understanding of its role in student development.